W-planner model and development: multi-agent online system applied to e-tourism (2005)
This work introduces the so-called tourist problem and presents a solution based on a multi-agent system. A group of agents that use a system to identify actions and plans is able to find the most appropriate itinerary for a tourist according to certain restrictions. Wireless devices are used for tourists to interact with the agent. ¿Variational calculus ¿techniques are used during the process to identify the set of possible solutions of the problem and techniques of ¿Jacobi fields¿ to find the solution ¿more easily replanable¿. This analytical method facilitates the identification of a tourist itinerary previously and is able to modify the proposed route at run time. Finally, the follow-up of a typical use case is shown, in which a tourist requests the W-planner under certain conditions the route best suited to their requirements.